The language of war - Rohach, Oksana; Рогач, Оксана (Східноєвропейський національний університет ім. Лесі Українки, 2015)
This article is devoted to the semantic, structural and etymological analysis of the language of war that reflects the relationship between the participants of various military conflicts with consideration of the ext ralinguistic factors that caused its appearance and usage. Special attention is paid to the fact that the language of war is stylistically marked and that is why every slur, every stereotype, every nationalistic and racist assumption is a war without weapo ns. Words of racist and nationalistic intolerance can hurt, and in world history there are many examples of effective propaganda and informational wars. Such words may only be the reason, but their effect is potentially lethal. That is why their power must be studied and taken into a consideration. An analysis of the language of war also presupposes studies of national history, international relations and economic and cultural relations. The extralinguistic factors, mainly the historic ones, which explain the reasons why such words came into being have been taken into consideration. Special attention has been paid to the most productive word building patterns according to which the analyzed words were coined, such as affixation, blending and different types of shortening. Здійснено семантичний, структурний та етимологічний аналіз лексики війни, яка віддзеркалює стосунки між учасниками різноманітних воєнних конфліктів, з урахуванням тих екстралінгвістичних факторів, що спричинили її появу та використання. Особливу увагу звернуто на той факт, що мова війни є стилістично маркованою, саме тому кожен дерогатив, кожен стереотип, кожне націоналістичне чи расистське переконання є «війною без зброї». Лексика расистської, націоналістичної нетерпимості може викликати образу чи біль, і в світовій історії багато прикладів ефективних пропагандистських та інформаційних воєн. Такі слова можуть бути лише причиною, проте їхній ефект – потенційно летальним, саме тому їхню силу необхідно брати до уваги та вивчати. Аналіз мови війни передбачає також вивчення національної історії, міжнародних стосунків, економічних та культурних зв‟язків, тому взято до розгляду екстралінгвістичні фактори,переважно історичні, які пояснюють, чому такі слова з‟явилися в мові. Особлива увага звернута на найпродуктивніші словотвірні моделі та зразки, за якими утворено аналізовані слова: афіксація, бленд инг та різні типи скорочень.
Мова війни
Keywords: language of war; national history; word building patterns; slur; stereotype; мова; війна; національна історія; упередження; словотвірні зразки; зневага; стереотип